Dietary Creatine Supplementation in Gilthead Seabream (Sparus aurata): Comparative Proteomics Analysis on Fish Allergens, Muscle Quality, and Liver - Schrama, Denise; Cerqueira, Marco; Raposo, Claúdia S.; Rosa da Costa, Ana M.; Wulff, Tune; Gonçalves, Amparo; Camacho, Carolina; Colen, Rita; Fonseca, Flávio; Rodrigues, Pedro M. (Frontiers in Physiology, 2018)
The quality of fish flesh depends on the skeletal muscle’s energetic state and delaying energy depletion through diets supplementation could contribute to the preservation of muscle’s quality traits and modulation of fish allergens. Food allergies represent a serious public health problem worldwide with fish being one of the top eight more allergenic foods. Parvalbumins, have been identified as the main fish allergen. In this study, we attempted to produce a low allergenic farmed fish with improved muscle quality in controlled artificial conditions by supplementing a commercial fish diet with different creatine percentages. The supplementation of fish diets with specific nutrients aimed at reducing the expression of parvalbumin can be considered of higher interest and beneficial in terms of food safety and human health. The effects of these supplemented diets on fish growth, physiological stress, fish muscle status and parvalbumin modulation were investigated. Data from zootechnical parameters were used to evaluate fish growth, food conversion ratios and hepatosomatic index. Physiological stress responses were assessed by measuring cortisol releases and muscle quality analyzed by rigor mortis and pH. Parvalbumin, creatine and glycogen concentrations in muscle were also determined. Comparative proteomics was used to look into changes in muscle and liver tissues at protein level. Our results suggest that the supplementation of commercial fish diets with In review 2 creatine does not affect farmed fish productivity parameters, or either muscle quality. Additionally, the effect of higher concentrations of creatine supplementation revealed a minor influence in fish physiological welfare. Differences at the proteome level were detected among fish fed with different diets. Differential muscle proteins expression was identified as tropomyosins, beta enolase, and creatine kinase among others, whether in liver several proteins involved in the immune system, cellular processes, stress and inflammation response were modulated. Regarding parvalbumin modulation, the tested creatine percentages added to the commercial diet had also no effect in the expression of this protein. The use of proteomics tools showed to be sensitive to infer about changes of the underlying molecular mechanisms regarding fish responses to external stimulus, providing a holistic and unbiased view on fish allergens and muscle quality.